Effect of intrinsic foot muscles training on foot function and dynamic postural balance: A systematic review and meta-analysis. - Zhen Wei; Ziwei Zeng; Min Liu; Lin Wang (PLoS ONE)
This systematic review aimed to analyse the effects of intrinsic foot muscle (IFM) training on foot function and dynamic postural balance. Keywords related to IFM training were used to search four databases (PubMed, CINAHL, SPORTDiscus and Web of Science databases.) for relevant studies published between January 2011 and February 2021. The methodological quality of the intervention studies was assessed independently by two reviewers by using the modified Downs and Black quality index. Publication bias was also assessed on the basis of funnel plots. This study was registered in PROSPERO (CRD42021232984). Sixteen studies met the inclusion criteria (10 with high quality and 6 with moderate quality). Numerous biomechanical variables were evaluated after IFM training intervention. These variables included IFM characteristics, medial longitudinal arch morphology and dynamic postural balance. This systematic review demonstrated that IFM training can exert positive biomechanical effects on the medial longitudinal arch, improve dynamic postural balance and act as an important training method for sports enthusiasts. Future studies should optimise standardised IFM training methods in accordance with the demands of different sports.